Perancangan Sistem Point Of Sales Multi Payment Berbasis Web Menggunakan Framework Laravel Pada UMKM Mr.Boba - Fikri Maulana Lathief; Hasdiana; Husni Lubis (LKP Unity Academy, 2023)
Mr.Boba is a company that sells various variants of drinks such as durian juice, boba and so on. The sales process is still done manually or handwritten and payment transactions can also only be done in cash. One of the obstacles that employees have faced is that customers want to pay non-cash but do not provide qris and the like. When employees process reports every time the store closes, it takes quite a long time. With this web-based point of sales system, it really helps employees to be faster and more efficient in their work. This system was built with the RAD method which is structured from requirement planning, workshop design and implementation and the framework used is the Laravel framework. Testing on this system shows good results with the blackbox testing method. The results of this study aim to facilitate employees to record both cash and non-cash transactions and computerized reports to umkm owners. Keywords : point of sales, multipayment, laravel, RAD, blackbox testing